Intramolecular hydrogen abstraction in radicals derived from inositol 1,3-acetals: efficient access to cyclitols - Murali, Chebrolu; Gurale, Bharat P.; Shashidhar, Mysore S. (European Journal of Organic Chemistry, 2010)
The benzylidene acetals obtained by cleavage of the orthobenzoate moiety in myo-mositol 1,3,5-orthobenzoate were used to prepare mono- as well as di-deoxy inositol derivatives via their xanthates. The dideoxygenation is a result of intramolecular abstraction of the benzylidene acetal hydrogen and subsequent cleavage of the acetal ring. Such a cleavage does not take place in analogous acetals derived from other orthoesters. The 1,3-acetals derived from myoinositol 1,3,5-orthoesters were also used to prepare neo-inositol and isomeric deoxy-amino inositols, Most of the reactions in these synthetic sequences starting from myo-inositol give one product in each step. The results presented here show that myo-inositol 1,3,5-orthobenzoate offers many advantages over other orthoesters for the synthesis of cyclitol derivatives from myo-inositol.
Keywords: cyclitols; Deoxygenation; Inosamine; Inositol; Radical reactions; Radicals; Xanthate